Microbubble flotation device for the capturing and culturing of H. Pylori from contaminated samples - Ng, Lucas Jia Yang (2018)
Helicobacter pylori (H. pylori) infects half the world’s population. Peptic and duodenal ulcers developed within infected individuals increases the risk of colon cancer. Our current methods in diagnosing the strain of H. pylori is contributing the growing resistance to antibiotic treatments. Thus, functionalized microbubbles are adopted as a diagnostic platform to capture and isolate H. pylori from contaminated yet easy to obtain patient samples. This final year project focuses on optimizing production procedures and microbubble formulation to generate suitable biotinylated microbubbles. Sonication (amplitude intensity of 117W) for 60s provides suitable cavitation conditions to disrupt larger microparticles continuously until a stable microbubble diameter is attained. Characterization of microbubbles are investigated and evaluated for the following criterion: structural integrity, abundance, size distribution, storage stability and membrane functionality. Sonication and differential centrifugation are employed to generate size isolated microparticles with high yield. Microbubbles were functionalized with biotin, enabling specific binding to avidin. Using avidin-FITC as a model for a functionalized H. pylori surface membrane specific antibody, the results in this manuscript indicate that the avidin-FITC conjugate onto the microbubble surface. Lower microbubble biotin composition reduced the frequency of monolayer folding on phospholipid shells. These results provide the initial steps in manufacturing stable functionalized microbubbles for H. pylori capture and isolation. With a diagnostic medium to efficiently identify specific bacterium strain, clinicians will be able to develop effective personalized treatments against H. pylori infections.